In silico screening of brazilian semiarid compounds to identify potential drugs with glucocorticoid receptor interaction - Côrtes Filho, Aldo Barbosa (2020)
The glucocorticoid receptor regulates the anti-inflammatory response, and prevents transcription of anti-inflammatory substances such as nuclear factor kB and lipocortin-1, IL-2, IL-6, TNF and prostaglandins. Thus, a search for new molecules with potential interaction with the glucocorticoid receptor is an interesting strategy for the treatment of inflammatory diseases. Virtual screening has proven to be a viable tool for discovering new products at lower cost and practicality. Thus, the aim of this study is to identify and evaluate brazilian semiarid compounds with anti-inflammatory potential with glucocorticoid receptor action through molecular coupling. Protein selection was performed by searching the 3D structure database, Protein Data Bank. A total of 382 semi-arid molecules available in the ZINC database of State University of Feira de Santana (UEFS) were used. Molecular docking was performed using Autodock Vina and as interaction clouds analyzed by the Discovery Studio Visualizer program. Mometasone furoate shows a binding energy of -12.7 Kcal.mol-1. A ZINC 69481862 molecule fits Lipinski and Veber rules, however, the best interaction was the ZINC 69482012 molecule, evidenced by the binding energy -11.2 Kcal.mol-1. Analyses of intermolecular interactions have shown that Van der Waals interactions and electrostatic bonds are crucial for the binding of the molecule at the receptor's active site. It is necessary to test in vitro to verify the viability and toxicity of the potential drug.